Serum Inflammatory Cytokines and Growth Factors in Patients with Sjögren’s Syndrome and Diabetes Mellitus - Yalçın Karaküçük; Sema Yilmaz; Ali Unlu; Banu Bozkurt; Şule Nur Acar Duyan (Genel Tıp Dergisi)
Abstract Background/ Aims: Sjögren’s syndrome (SS) and diabetes mellitus (DM) are common causes of dry eye disease (DED) and autologous serum is used when artificial tears are not sufficient. Our aim was to compare serum growth factor and inflammatory cytokine levels of SS and DM patients with the healthy individuals. Methods: Twenty-three SS patients (mean age 52.70±7.55 years), 25 DM patients (mean age 56.68±6.53 years), and 23 healthy subjects (mean age 51.70±9.14 years) were included in the study. After detailed ophthalmological examination, Schirmer test, tear break-up time (TBUT) and Ocular Surface Disease Index (OSDI) scores were measured. Serum levels of six different proinflammatory interleukins (IL), five growth factors, matrix metalloproteinase-9, and fibronectin were measured by immunoassay. One-way ANOVA or Kruskal-Wallis tests and Dunn-Bonferroni post hoc analysis were used for comparison and p<0.05 was considered significant. Results: Schirmer test and TBUT were significantly lower in the SS group (2.08±1.72 mm/5 min and 3.08±2.08 s) than in the DR (10.24±4.63 mm/5 min and 4.20±3.09 s) and control groups (13.30±5.95 mm/5 min and 9.00±1.75 s) (p<0.001). Among the parameters studied, mean serum IL-23 level was significantly higher in the SS group (156.66±207.94 pg/mL) than in the DM and control groups (73.48±95.91 and 69.59±105.39 pg/mL, respectively) (p<0.05). Serum insulin-like growth factor 1 (IGF-1) level was lowest in DM patients (DM: 12.89±21.09, SS: 30.77±19.85, and control: 27.08±21.93 ng/mL) (p<0.05). Sjögren’s syndrome disease activity index (ESSDAI) showed a negative correlation with TBUT and a positive correlation with IL-1, IL-2 and fibronectin (p<0.005). Conclusions: Except IL-23 and IGF-1, the contents of serum obtained from patients with SS and DM are similar with the healthy individuals. Therefore, autologous serum seems to be a good option to replace deficient tear fluid in these subjects.